Strategi Adaptasi Ekonomi Petani Penggarap terhadap Dampak Pembangunan Jalan Tol - Rifky Achmad Julio; Oekan S. Abdoellah (Universitas Padjadjaran, 2022)
The construction of Bogor-Ciawi-Sukabumi (Bocimi) toll road has indirectly affected peasants of Kampung Asri in Bogor Regency. The groundwater flow has decreased since the construction began and affected rice field irrigation. The waterways have been constructed to overcome this problem, however there were damages and water decrease continues to occur. The shortage of water led the land owners to sell their properties, which can not be cultivated for rice farming, to developers. As a consequence peasants lost their source of income. This study describes the socio-cultural adaptive strategy of peasants at Kampung Asri who lost their source of income. This study applied a qualitative method. Data were collected through secondary data collection, observation, and in-depth interviews. The findings of this study suggest that peasants of Kampung Asri changed their farm commodity and type of income generating activities to adjust to the changing situation. This strategy depicts their adaptive strategy to save their livelihood.